Long-Term Follow-Up of Two-Phase Orthodontic Treatment of Class II Malocclusions - Abdullah Demir; Faruk A. Başçiftçi; Serdar Üşümez; Yaşar Göyenç (Turkish Journal of Orthodontics, 2010)

(untitled)
Aim:The aim of the study was to investigate the stability of dentoskeletal changes 8 years after treatment with the activator appliance, followed by an edgewise appliance.Subjects and Methods:The study comprised 18 children (10 boys and 8 girls at 12.2±1.4 years of age) with a skeletal Class II pattern and a Class II molar relationship. Pre-treatment (T1) their ANB angles were greater than 4 degrees and overjets greater than 7 mm. Standardized lateral cephalograms were taken in centric occlusion at the start of treatment (T1), at the end of activator treatment (T2), at the end of fixed appliance therapy (T3) and 6.2 years after the removal of the fixed appliances (T4). Ten angular and nine linear cephalometric measurements were determined. A paired-sample t-test was used to evaluate the treatment changes.Results:At the end of active treatment period (T3) the skeletal relationship was improved and there were significant (p=0.000) increases in maxillary and mandibular length (Co-A and Co-Gn) and SNB. The upper incisors were significantly (p=0.023) uprighted and retruded (U1-NA). SNA and ANB angles were significantly (p=0.012, p=0.000 respectively) decreased whereas IMPA and mandibular plane angle (Go-Gn-SN) remained stable. At (T4) the changes were generally in agreement with those T3 at except for a slight return to the original values for SNA and A to N -I FH (mm) measurements.Conclusion:The anteroposterior dentoskeletal changes obtained with the activator appliance followed by fixed edgewise appliances were demonstrated to be stable over 6.2 years.